Trust—Factors that have an impact on the interrelations between members and employees in rural cooperatives. Issue 2 (December 2018) - Jensen-Auvermann, Tessa; Adams, Isabel; Doluschitz, Reiner
Highlights: It is important that trust is strategically noticed in a rural cooperative. Some factors that increase members' trust towards the employees that represent the rural cooperative are identified. Trust supports the exchange of information between members and employees within a rural cooperative. The MemberValue model can also be used for rural cooperatives. Abstract: In the course of growth, even across national borders, the relationship between the cooperative and its members can become less close and, in addition, rural cooperatives are mainly service companies. Trust is an important factor for service companies. Within this context, it would be interesting to know how to improve structures that foster trust within a cooperative. This study treats members and employees of the same German cooperative as an experimental case. A total of 566 members and 1250 employees within the organization responded to the questionnaire, based on the MemberValue model, in the summer of 2016. Regression analyses identified factors such as transparency and service quality that have an impact on trust expressed by members towards employees that represent the rural cooperative. This study also investigated how trust affects the exchange of information within members and employees of a rural cooperative.